Research on Abnormal Ultra-shallow Shutdown of Undersea Vehicles - Hou-quan LI; Xiao-tao FENG; Xiao-fang ZHANG; Zhi-bo ZHAO (水下无人系统学报)
Concerning the problem of abnormal ultra-shallow shutdown protection, undersea vehicles navigate at a set depth even if they are not navigating at ultra-shallow protection depths. Various factors that may lead to the abnormal shutdown of undersea vehicles are analyzed. The numerical simulation method is used to analyze the effect of fluid pressure on different positions of the underwater vehicle at different speeds. The distribution law of hydrodynamic errors, which are observed when an abnormal shutdown of undersea vehicles occurs, is obtained based on sea trial data. The numerical simulation and the trials indicate that, when the vehicle navigates near the minimum depth, there will be a fluid pressure difference between the front and back depth transducers on the vehicle, which varies with the speed of the vehicle. When the speed of the vehicle exceeds a certain value, the fluid pressure error will be so large that the back depth transducer will indicate a normal depth while the front transducer will indicate an ultra-shallow state, thus resulting in an abnormal shutdown.